Dynamics of Constraints: Essays on Notation, Editing and Performance - Assis, Paulo de; Kanno, Mieko; Parra Cancino, Juan (Leuven Universitaire Pers Leuven, 2009)
The three essays of Dynamics of Constraints express some fundamental issues addressed by ORCiMs research group the musicians relation to notation. Paulo de Assis argues that critical editions should generate critical users, advocating for a new kind of editor and performer; Mieko Kannos contribution reflects the rapid expansion of the use of electronics in contemporary music, stating that every new work creates an original compositional environment, where the performers movement-sound co-ordination is given a new significance, while Juan Parra Cancino points towards a kind of composition, where both the performing and the listening experience don't aim to achieve a 'final' version of the piece an entity that might ever manifest.
Keywords: Notation; Urtext edition; Performance; Artistic research